Psychometrics and Life History Strategy: The Structure and Validity of the High K Strategy Scale. (1st January 2014) - Copping, Lee T.; Campbell, Anne; Muncer, Steven
In this paper, we critically review the conceptualization and implementation of psychological measures of life history strategy associated with Differential K theory. The High K Strategy Scale (HKSS:Giosan, 2006 ) was distributed to a large British sample ( n = 809) with the aim of assessing its factor structure and construct validity in relation to theoretically relevant life history variables: age of puberty, age of first sexual encounter, and number of sexual partners. Exploratory and confirmatory factor analyses indicated that the HKSS in its current form did not show an adequate statistical fit to the data. Modifications to improve fit indicated four correlated factors (personal capital, environmental stability, environmental security, and social capital). Later puberty in women was positively associated with measures of the environment and personal capital. Among men, contrary to Differential K predictions but in line with female mate preferences, earlier sexual debut and more sexual partners were positively associated with more favorable environments and higher personal and social capital. We raise concerns about the use of psychometric indicators of lifestyle and personality as proxies for life history strategy when they have not been validated against objective measures derived from contemporary life history theory and when their status as causes, mediators, or correlates has not been investigated.